FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIVITAS PANGLIMA LAOT DALAM PENGELOLAAN SUMBER DAYA ALAM LAUT DI KOTA SABANG - Andri Kurniawan (Jurnal Dinamika Hukum, 2008)
At Nanggroe Aceh Darussalam Province, regional domination pattern of sea still very strong grow in fisherman society. Therefore, in their society still functioned Panglima Laot that have the function to : defence and observe the sea for regional exploiting. In this case, the authoritative of Panglima Laot, first, maintaining the sea environment as cooperative ownership ( common heritage). Second, arrange the resource management of the sea. Third, give the sanction to the people that  collision to rule of the customary law of the sea. In Implementated their function, Panglima Laot have a lot of constraint, such as : the factor of fishing in sea, institution factor, the earningsinstitute factor, regional boundary factor, human resource factor, factor of the weakness management system in effort fishery, and also factor of supply of the traditional arrest. Kata Kunci : Panglima Laot dan Pengelolaan SDA Laut